Anonymous asked in Science & MathematicsMathematics · 1 decade ago

can any one help i need to check if this is correct finding y explicitly as a function of x?

find y explicitly as a function of x express the equation in the form y=f(x) ln(3-y)=3ln(2x+1)-x heres my answer if any one can tell me if im correct and if im wrong can some one give me some help thanks.


exp ln(3-y)=exp 3ln(2x+1)-x

y=exp 3ln(2x+1)-x


=exp (ln(2x^3+1))/exp


if any one can give me a few tips thanks.

3 Answers

  • 1 decade ago
    Best Answer

    wait... i want to clarify...

    is this

    ln(3-y) = {3ln(2x+1)} - x

    in such a case you cannot combine the 2nd term to the logarithmic term...

    but some properties first...

    n logA = log (A^n)

    e^(A+B) = e^A*e^B


    ln(3 - y) = {3ln(2x+1)} - x

    ln(3 - y) = {ln(2x+1)^3} - x

    e^ln(3-y) = e^[ {ln(2x+1)^3} - x ]

    (3 - y) = e^ln[(2x+1)^3] e^(-x)

    3 - y = (2x-1)^3 e^(-x)

    y = 3 - {(2x-1)^3 e^(-x)}


  • Anonymous
    1 decade ago

    hello! i think it should be looks that:

    ln(3-y) = 3ln(2x+1)-x

    exp ln(3-y) = exp [ 3ln(2x+1)-x ]

    (3-y) = exp [ ln(2x+1)^3-x ]

    where exp(b1)-exp(b2)=exp(b1)/exp(b2)


    (3-y) = exp [ ln(2x+1)^3 ] / exp(x)

    where exp(b)=e^b ,e^b=c where c is positive constant


    3-y = (2x-1)^3 / e^x

    y = 3-[ (2x-1)^3 / e^x ]

  • Anonymous
    1 decade ago

    yes you can take home work help also yes they will help you sure and the provide u FREE session This is the link of and if u want math help they can sure help you just click on this and have FREE session and you can have FREE worksheets as well i am using it and getting best grades my mail id is

Still have questions? Get your answers by asking now.